2020
DOI: 10.1136/bmj.m1541
|View full text |Cite
|
Sign up to set email alerts
|

What organisations around the world are doing to help improve doctors’ wellbeing

Abstract: chief executive of NHS Practitioner Health, says, "At this difficult time for doctors and the NHS workforce it feels natural that we at Practitioner Health explore how we can use our experience to support and help."We're focusing initially on enabling staff to connect, as we feel many of the anxieties and fear being expressed will be similar for many people. With this in mind, we're creating a range of online events, webinars, and groups to act as a space to talk, share, learn, and care for one another.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…During the COVID-19 outbreak, this tendency might have changed. 9,24 The social recognition HPs are receiving during this pandemic together with the the mass and social media diffusion of their testimonies could help to lower the internal psychological barriers to seeking professional aid if necessary. However, when it comes to severe mental disorders, self-stigmatizing attitudes may persist.…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 outbreak, this tendency might have changed. 9,24 The social recognition HPs are receiving during this pandemic together with the the mass and social media diffusion of their testimonies could help to lower the internal psychological barriers to seeking professional aid if necessary. However, when it comes to severe mental disorders, self-stigmatizing attitudes may persist.…”
Section: Discussionmentioning
confidence: 99%
“…There are notable parallels between environments designed for staff wellbeing, and the preventative and de-escalating 'sensory rooms' and 'comfort rooms' that are already used with patients, in psychiatric inpatient environments [16][17] and to support self-management in people with chronic conditions, such as long-term pain. In addition to physical spaces, some trusts are offering virtual wobble rooms for healthcare workers, providing regular online group-based support focused on honest expression of feelings and self-care [18].…”
Section: Dedicated Wellbeing Centresmentioning
confidence: 99%
“…Self-medication, denial and rationalisation may be initial defence mechanisms used to confront stressful situations but may result in failure to seek help when being exposed to mental health harm. 10 Feeling of solitude and despair arise following immense pressure from these factors and lead to mental agony, impatience, anxiety, depression and mental fatigue. 11 In this study, we found that a significant number of HCWs fell prey to anxiety, stress and depression.…”
Section: E295mentioning
confidence: 99%